A STUDY OF THE ENGLISH CREATIVITY AT THE COMMERCE COLLEGE STUDENTS OF THE AHMEDABAD DISTRICT - Chauhan, Harshida Rameshsingh; Fatnani, Kinjal; Sathvara, Nilesh P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Creativity in the arts is characteristically intensely personal and reflects both the feelings and the ideas of the artist. By contrast, English creativity is always constrained by self-consistency, by trying to understand nature and what is already known. A work of art is capable of many readings, of multiple interpretations, whereas English discoveries have a strictly defined meaning; artistic creations are about singular, often internal, experiences, whereas scientists strive for generality, there are objective and shared criteria for judging English work.